Electro-Mechanical Testing of Conductive Materials Used in Flexible Electronics - Cordill, Megan J.; Glushko, Oleksandr; Putz, Barbara (Frontiers in Materials, 2016)
The use of flexible electronics has increased in recent years. In order to have robust and long lasting flexible displays and sensors, the combined electro-mechanical behavior needs to be assessed. The most common method to determine electrical and mechanical behavior of conductive thin films used in flexible electronics is the fragmentation test, or uniaxial tensile straining of the film and substrate. When performed in situ fracture and deformation behavior can be determined. The use of in situ electrical resistance measurements can be informative about the crack onset strain of brittle layers, such as transparent conductors, or the stretchability of metal interconnects. The combination of in situ electrical measurements with in situ X-ray or confocal laser scanning microscopy can provide even more information about the failure mechanisms of the material systems. Lattice strains and stresses can be measured with X-rays, while cracking and buckle delaminations can be studied with confocal laser scanning microscopy. These new combinations of in situ methods will be discussed as well as methods to quantify interfacial properties of conductive thin films on polymer substrates. The combined techniques provide valuable correlated electrical and mechanical data needed to understand failure mechanisms in flexible devices.